Asymmetric Synthesis of Tetracyclic Pyrroloindolines and Constrained Tryptamines by a Switchable Cascade Reaction - de Graaff, Corien; Bensch, Lisa; Boersma, Sjoerd J.; Cioc, Răzvan C.; van Lint, Matthijs J.; Janssen, Elwin; Turner, Nicholas J.; Orru, Romano V. A.; Ruijter, Eelco (Angewandte Chemie, 2015)
The interrupted Fischer indole synthesis of arylhydrazines and biocatalytically generated chiral bicyclic imines selectively affords either tetracyclic pyrroloindolines or tricyclic tryptamine analogues depending on the reaction conditions. We demonstrate that the reaction is compatible with a variety of functional groups. The products are obtained in high optical purity and in reasonable to good yield. We present a plausible reaction mechanism to explain the observed reaction outcome depending on the stoichiometry of the acid mediator. To demonstrate the synthetic utility of our method, pharmaceutically relevant examples of both product classes were synthesized in highly efficient reaction sequences, including a phenserine analogue as a potential cholinesterase inhibitor and constrained tryptamine derivatives as selective inhibitors of the 5‐HT6 serotonin receptor and the TRPV1 ion channel. Am Scheideweg: Unterbrochene Fischer‐Indolsynthesen mit Arylhydrazinen und chiralen bicyclischen Iminen ergeben abhängig von den Reaktionsbedingungen selektiv entweder tetracyclische Pyrroloindoline oder tricyclische Tryptamin‐Analoga. Die optisch hoch reinen Produkte lassen sich leicht in medizinisch bedeutende Verbindungen umsetzen.